A history of studies of reproductive isolation between Drosophila pseudoobscura and D. persimilis - Stewart Leigh; Michael G. Ritchie (Fly)
Drosophila pseudoobscura and D. persimilis are a sister species pair that have been used as a model for studies of reproductive isolation and speciation for almost 100 years owing to their close evolutionary history, well characterized genetic differences, and overlapping geographic distribution. There are extensive analyses of both pre- and post-zygotic isolation, including studies of courtship divergence, conspecific sperm precedence (CSP) and how reinforcement by natural selection may or may not act to strengthen isolation in sympatry. Post-zygotic analyses explore the underlying mechanics of reproductive isolation; how inversions may give rise to initial speciation events and misexpression of key genes typically found within inversion regions render hybrid offspring unfit or inviable. We aim here to present a history of studies of reproductive isolation between this species pair, looking at how the field has developed over the last century and identifying the open questions and gaps within the literature.